NISHAH KELAMIN, HUBUNGAN PANJANG-BERAT DAN UKURAN REPRODUKSI HIU Hexanchus spp. DI PERAIRAN SELATAN NUSA TENGGARA - Sentosa, Agus Arifin (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Hexanchus spp. are shark species that are often caught in the Indian Ocean southern Nusa Tenggara and its status is Near Threatened, but the information is still relatively limited. This study aimed to sex ratio, length-weight relationship and reproductive size of sixgill shark, Hexanchus spp. caught from southern Nusa Tenggara waters. This study had been carried out during 2016 at the Fishing Port of Tanjung Luar, East Lombok, West Nusa Tenggara. Shark data collection was done by measuring the length, weight, maturity and fishing data. Data were analyzed by formula of sex ratio, length-weight relationship, length at first maturity (Lm) and length at first catch (Lc). The results showed that Hexanchus spp. caught in the southern Nusa Tenggara waters consisted of H. nakamurai (81.82%) and H. griseus (18.18%). The sex ratio of both sharks was dominated by the female. The average of the total length of H. griseus (218.3 ± 96.08 cm). It was longer than H. nakamurai (127.6 ± 30.35 cm). The length-weight relationship of H. griseus was formulated as W = 0.0195 LT 2,6344 (R² = 0,9265) and H. nakamurai with the formula W = 0.002 LT 3,1098 (R² = 0.902). Both species have the size of Lm was bigger than the size of Lc which indicated to their population vulnerability.